Briefly highlighting some unseen evidence of two comorbid COVID-19 patients - Abdullah; Salman, Muhammad; Ali, Sher; Muhammad, Riaz; Waheed, Aiman; Khan, Muddasir; Ullah, Sana; Oliveira, Carlos Augusto Fernandes de (Brazilian Journal of Case Reports, 2024)
In recent years, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has caused substantial morbidity and mortality worldwide. Comorbidities have negatively impacted the pandemic of coronavirus disease 2019 (COVID-19). This case report discusses the data of two deceased individuals with COVID-19 and pre-history of chronic infections in Pakistan. COVID-19 positivity of the patients was based on RT-PCR at early hospitalization. Similarly, the patients were undergone through the chest X-ray, which exposed COVID-19 pneumonia with left lung effusion. All laboratory parameters including hematologic (e.g., total leucocyte count and hematocrit) and inflammatory biomarkers (e.g., C-reactive protein, prothrombin time, activated partial thromboplastin clotting time, D-dimer and serum ferritin) of the deceased candidates were highly abnormal on day one onward. Septic shock, neutrophilia, lymphopenia, thrombocytopenia and leukocytosis were evident in both cases. Despite giving full-fledged treatments, patients conditions deteriorated rapidly, retaining CO2 with low oxygen saturation. Blood pressure and oxygen saturation markedly dropped and turned to cardiopulmonary arrest at the final stages in each case. These findings confirm the impact of comorbidities on COVID-19 severity, based on remarkable changes in laboratory parameters. Current report suggests extensive monitoring of COVID-19 comorbid individuals to reduce morbidity and mortality.